2014
DOI: 10.1007/s00256-014-1899-1
|View full text |Cite
|
Sign up to set email alerts
|

Thanatophoric dysplasia. Correlation among bone X-ray morphometry, histopathology, and gene analysis

Abstract: The correlated observations of X-ray morphometry, histopathology, and gene analysis prompted the following diagnostic workup for TD: (1) prenatal sonography suspicion of skeletal dysplasia; (2) post-mortem X-ray morphometry for provisional diagnosis; (3) confirmation by genetic tests (hot-spot exons 7, 10, 15, and 19 analysis with 80-90% sensibility); (4) in negative cases if histopathology confirms TD diagnosis, research of rare mutations through sequential analysis of FGFR3 gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…Thanatophoric dysplasia (OMIM 187600) is the most frequent sporadic lethal skeletal dysplasia with a prevalence of about 1 in 17 000-50 000 births [1]. Characteristic features of TD include markedly shortened limbs, narrow thorax with short ribs but normal trunk length, macrocephaly with frontal bossing, and low depressed nasal bridge [1,24]. It has been shown that expected mutations in TD include p.Arg248Cys, p.Tyr373Cys and p.Lys650Glu mutations [23].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thanatophoric dysplasia (OMIM 187600) is the most frequent sporadic lethal skeletal dysplasia with a prevalence of about 1 in 17 000-50 000 births [1]. Characteristic features of TD include markedly shortened limbs, narrow thorax with short ribs but normal trunk length, macrocephaly with frontal bossing, and low depressed nasal bridge [1,24]. It has been shown that expected mutations in TD include p.Arg248Cys, p.Tyr373Cys and p.Lys650Glu mutations [23].…”
Section: Discussionmentioning
confidence: 98%
“…All of the dysplasias display common phenotypic characteristics with different grades of severity [22]. (1) Pulmonary hypoplasia, immature kidneys Osteogenesis imperfecta (1) Cliteromegaly, immature kidneys Jarcho-Levin syndrome (1) Pulmonary hypoplasia Arthrogryposis (1) Agenesis of cerebellum, dilatation of bilateral cerebral ventricules, hypoplasia of psoas muscle Dysostosis (24) Abdominal wall: Omphalocele, gastroschisis Craniofacial: cleft-lip and palate, dysplastic ears, micrognathia, low-set ears, depressed nasal bridge, agenesis of external auditory channel, agenesis of the nose, agenesis of right eye-lid. Categorizing SDs is important because some of them are lethal.…”
Section: Discussionmentioning
confidence: 99%
“…Un estudio publicado en 2014 muestra que la identificación prenatal de displasia del lóbulo temporal podría ayudar en la identificación de DT, demostrado su presencia en el 67% de los casos analizados. Esto ha sido corroborado posteriormente por otros trabajos (17,(19)(20)(21). La tomografía computada 3D prenatal contribuye al diagnóstico y podría tener un rol complementario a la US (22).…”
Section: Discussionunclassified
“…If hot spot exons are negative, then a search for rare mutations using sequential analysis of FGFR3 gene is performed. [37] The nucleotide sequence of FGFR3 is highly conserved between man and mouse.…”
Section: Antenatal Diagnosis In Tdmentioning
confidence: 99%
“…Interplay between mechanical factors and the effects of the underlying mutation are additional factors in this process. [9] …”
Section: Manifestationsmentioning
confidence: 99%